Participatory Action Research for Developing Facilitator to Driving Sufficiency Economy Community for the Officer at Rangkayai Municipality, Phimai District, Nakhonratchasima - ปรีชานันท์, ชิดชนก (Ratchaphruek Journal, 2017)
ABSTRACT The objectives of this study were 1) to investigate the operational potential of finding guidelines for developing process facilitators and 2) to evaluate the results of implementing the guidelines for developing process facilitators of officials at Rung KaYai Municipality, Phimai District, Nakhon Ratchasima, to drive into sufficiency economy communities. Data were collected from 30 Rung KaYai Municipality’s officials using participatory action research method. Percentage and mean were analyzed for quantitative data and inductive method was used for qualitative analysis. The results showed that the overall operational potential of the target group was at the moderate level. Considering by issues, the understanding about process facilitator was at the low level, while the knowledge about sufficiency economy philosophy and the desire to become a process facilitator driving sufficiency economy community were both at the moderate level. The results suggested that the action trainings on how to implement sufficiency economy philosophy for the officials should be practiced. Guidelines for developing process facilitators included organizing participatory action trainings about sufficiency economy philosophy and the roles of a process facilitator. The evaluation of the guidelines’ implementation for facilitator development process with the officials showed that after the action participatory training, Rung KaYai Municipality’s officials realized the important process of the facilitator’s roles in driving the sufficiency economy community in the area.